Metabolism of carotenoid and its regulation in garden crop - TAO Jun; ZHANG Shang-long (浙江大学学报. 农业与生命科学版, 2003)
Carotenoids constitute one of the most important classes of plant pigments and have a range of diverse functions and actions, especially in relation to human health. They play a crucial role in defining the quality of fruit and vegetables and the decorative value of flower. This review article introduces the recent advances in study on gene regulation of carotenogenesis and effects of environment and chemicals on carotenogenesis in garden crop such as citrus, tomato, marigold and so on.